Generation COVID-19 and bodily disorders: Hyperbolic narratives and a developmental psychopathology perspective - D'Agostino, Alessandra; Gritti, Emanuela Saveria; Gagliardi, Chiara (Frontiers in Public Health, 2022)
Starting from spring 2020, newspapers headlines and studies have suggested that the Covid-19 pandemics had a relevant negative impact especially on the mental health of children and adolescents, so that terms like “lost generation” or “generation Covid” have been used to define youth in time of pandemic crisis. In fact, international health agencies report an increase in depression and anxiety among adolescents in Covid time, but also a rise in bodily disorders, such as nonsuicidal self-injury and eating disorders. However, scientific data on this matter are not as clear as they seem. Focusing specifically on bodily disorders in adolescents during Covid-19, the aim of this perspective paper is to review it and propose a novel viewpoint on this issue. Firstly, data regarding frequency and phenomenology of bodily disorders in adolescence before and during the pandemic will be presented to underline possible discrepancies, gaps, or hyperbolic descriptions in the literature published after the Covid outbreak. Secondly, a specific theoretical-clinical perspective will be proposed, that is, a developmental psychopathology perspective which attempts to frame these phenomena in a more nuanced and complex way, taking into account the role of developmental processes in adolescence age and its difficulties in the specific, subjective life-context of the individual, when intertwining with vulnerability factors and stressful life events. As such, we highlight the function of the body for the adolescent as a primary mean for regulating the self-other relationship and developing a greater sense of self-agency.